Brandon Sanderson’s linguistic ingenuity: grounding occasionalisms and their derivational potential - Altynbekov, A.M.; Mazhitayeva, Sh.; Khan, N.K. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2025)
A comprehensive approach to studying Brandon Sanderson’s works allows the authors of the article to conduct an original analysis of the methods of forming occasionalisms as derivatives involved in creating unique figurative units within the writer’s worldview. The study of derivational morphology made it possible to identify the features of word-formation processes used in shaping Sanderson’s worldview, including compounding, affixation, complex formation, and blending. The results of the study provide a deeper understanding of the author’s linguistic creativity and its significance for contemporary literature. The findings indicate that compounding is the dominant strategy, enabling semantic transparency and intuitive understanding for readers, while affixation and blending play a minor role in lexical innovation. In the presented work, the authors highlight the role of grounding in the emergence of new lexical units, demonstrating the process of lexical items transitioning from an activated to an established concept. This process influences how occasionalisms are perceived and integrated into the narrative. Initially perceived as foreign or inventive (e.g., spren, chull), such words evolve into functional elements of the fictional world through repetition and narrative embedding. Conversely, already familiar lexical units (e.g., storm, shard, mist) may undergo contextual redefinition, acquiring new in-universe meanings and emotional weight. The study also distinguishes between primary occasionalisms (authorial neologisms serving as base words) and grounded (derived) occasionalisms, which are formed from them through additional semantic or structural transformations. Derived occasionalisms, in turn, are divided into ordinary ones — where existing words undergo shifts in meaning — and pure ones, which arise directly from the original occasionalisms. This classification provides a framework for tracing the semantic and morphological evolution of invented vocabulary. Ultimately, the study underscores the dynamic interplay between language and storytelling, demonstrating how occasionalisms not only function as markers of a linguistic personality but also serve as tools for immersive worldbuilding. The findings contribute to the broader field of fictional morphology and speculative fiction linguistics, illustrating how fictional languages mirror real-world derivation while maintaining their unique narrative functions. The analysis of Sanderson’s lexicon offers valuable insights into the creative potential of neologisms in fiction and emphasizes their role in shaping the overall depth of a fictional universe.
Брендон Сандерсонның лингвистикалық тапқырлығы: негізделген окказионализмдер және олардың туынды әлеуеті
Лингвистическая изобретательность Брендона Сандерсона: обоснование окказионализмов и их деривационный потенциал
Keywords: occasionalism; linguistic creativity; authorial words; derivates; speech; linguistic personality; grounding; blending